GE_GERICHTE P/15113/2016 vom 17. August 2018 - GE Cour de justice (2018)
DISPOSITIONS PÉNALES DE LA LCR ; EXCÈS DE VITESSE ; SIGNALISATION ROUTIÈRE ; ERREUR DE DROIT(DROIT PÉNAL) | LCR.90.al1; LCR.27.al1; OSR.108.al5.letA; CP.21